Teaching English allomorphs through ‘Harry Potter and the Chamber of Secret’ movie - Asfi Aniuranti; Tono Suwartono (EduLite: Journal of English Education, Literature and Culture, 2020)
The study is primarily concerned with the use of ‘Harry Potter and the Chamber of Secret’ to teach English allomorphs in EFL classrooms. This paper is an alternative way to teach them as a significant element of pronunciation. The types examined are Regular Past Tense, Regular Plural Number, Third Person Present, The Regular Possessive, and Reduced IS and HAS. Besides the main highlight of allomorph pronunciation, the movie also contemplates some suprasegmental features called word stress and sentence intonation. The teachers may also utilize the movie through four phases. They are warm-up activity, completion, categorization, and production. Bringing a movie that has many benefits into EFL classrooms may lead to a good comprehension of English allomorphs to the students.